Circulating endothelial cell levels in psoriatic patients and their modification after an anti‐TNF‐alpha (Etanercept) treatment. (18th March 2013) - De Simone, C.; Caldarola, G.; Coco, V.; Palumbo, S.; Pocino, K.; Sgambato, A.; Maiorino, A.; Corbi, M.; Sandri, M.T.; Vendittelli, F.; Capoluongo, E.
Abstract Background Endothelial function in psoriatic patients has been mainly evaluated through a high‐resolution ultrasound measurement of flow‐mediated vasodilation in the brachial artery, which is an operator‐dependent and technically demanding technique: this characteristic, together with different patient selection criteria, could account for the conflicting results emerging from different studies. Recently, Circulating Endothelial Cells (CECs) level has been suggested as a novel biomarker of vascular injury. Methods The number of CECs was determined by a semi‐automated immunomagnetic system (CellSearch system) in peripheral blood of psoriatic patients (n = 48) and healthy subjects (n = 50). In 15 patients, CEC level was also evaluated after 6 months of treatment with an anti–TNF‐alpha agent, Etanercept. The plasma levels of high‐sensitivity C‐reactive Protein (CRP), E‐selectin, VEGF and PAI‐1 were measured by ELISA. The psoriasis severity was assessed by PASI score. Results A statistically significant difference (P = 0.001) was found between CEC level in psoriatic patients (10.6 ± 9.4 cells/mL) vs. the control group (3.9 ± 0.9 cells/mL). This count inversely correlated with sE‐selectin levels (r2 = 0.16; P = 0.03). After 6 months of therapy, patients experienced a significant (P < 0.05) decrease in CEC levels (3.4 ± 1.3 cells/mL) and in PASI score (from 11.7 ± 8.1 to 2.1 ± 4.0). Conclusions The elevated CECs level that we found in a sample of high selected psoriatic patients could be expression of endothelial damage. Lowering of CECs count after treatment with Etanercept support the hypothesis that an effective systemic therapy of psoriasis may also improve the endothelial function.